Characterizing the genetic diversity and population structure of Plasmodium knowlesi in Aceh Province, Indonesia - Pinkan P. Kariodimedjo; Nadia Fadila; Sydney R. Fine; Hidayat Trimarsanto; Chris Cotter; Leily Trianty; Michelle S. Hsiang; Jennifer Smith; Adam Bennett; Rintis Noviyanti; Farah N. Coutrier (PLoS ONE, 2025)
As in other parts of Southeast Asia, efforts to achieve or sustain malaria elimination in Indonesia have been threatened by the emergence of human infection with the primate species P. knowlesi. To understand the transmission dynamics of this species, investigation of P. knowlesi genetic diversity and population structure is needed. A molecular surveillance study was conducted in two phases between June 2014 and September 2018 at five primary health facilities in Aceh Province, Indonesia, an area nearing malaria elimination. Dried blood spot samples were collected from patients presenting with suspected malaria and testing positive for malaria by microscopy. PCR was performed for molecular confirmation and species identification. Forty-six samples were confirmed to be P. knowlesi, of which 41 were amplified with genotyping targeting ten known P. knowlesi microsatellite markers. For samples within a site, nearly all (9 of 10 loci) or all loci were polymorphic. Across sites, multiple identical haplotypes were observed, though linkage distribution in the population was low (index of association (IAS) = 0.008). The parasite population was indicative of low diversity (expected heterozygosity [HE] =  0.63) and low complexity demonstrated by 92.7% monoclonal infections, a mean multiplicity of infection of 1.06, and a mean within-host infection fixation index (FST) of 0.05. Principal coordinate and neighbour-joining tree analyses indicated that P. knowlesi strains from Aceh were distinct from those reported in Malaysia. In a near-elimination setting in Indonesia, we demonstrate the first evidence that P. knowlesi strains were minimally diverse and were genetically distinct from Malaysian strains, suggesting highly localized transmission and limited connectivity to Malaysia. Ongoing genetic surveillance of P. knowlesi in Indonesia can inform tracking and planning of malaria control and elimination efforts.